2020
DOI: 10.2147/hiv.s232146
|View full text |Cite
|
Sign up to set email alerts
|

<p>First Report on HHV-6 Infection Among HIV-Infected Individuals Residing in Surabaya, Indonesia</p>

Abstract: Background: Morbidity and mortality from acquired immunodeficiency syndrome (AIDS) are often associated with the reactivation of a herpes virus infection. Human herpesvirus-6 (HHV-6) is usually common in childhood infections that remain latent and can act as opportunists during immunosuppression to reactivate and cause disease. In human immunodeficiency virus (HIV)-infected patients, the impact of HHV-6 infection can be an upregulator of HIV replication and accelerate progress towards AIDS. However, studies on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…For HIV-infected children, a study in Brazil reported that HHV-6 was detected in 18% of the oral mucosa [ 13 ]. Other studies using plasma samples have reported that the frequency of HHV-6 ranges from 7% to 32.2% [ 1 , 52 , 53 ]. HHV-6 infection/reactivation in HIV/AIDS individuals causes disseminated infections in many organs, leading to a variety of diseases, including encephalitis, pneumonitis, multiple sclerosis, non-Hodgkin’s and Hodgkin’s lymphomas, and other serious diseases [ 3 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…For HIV-infected children, a study in Brazil reported that HHV-6 was detected in 18% of the oral mucosa [ 13 ]. Other studies using plasma samples have reported that the frequency of HHV-6 ranges from 7% to 32.2% [ 1 , 52 , 53 ]. HHV-6 infection/reactivation in HIV/AIDS individuals causes disseminated infections in many organs, leading to a variety of diseases, including encephalitis, pneumonitis, multiple sclerosis, non-Hodgkin’s and Hodgkin’s lymphomas, and other serious diseases [ 3 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both variants of HHV‐6 are related to neurological diseases, although they have different tropisms and pathogenicity 8 . Following initial infection, HHV‐6 may spread in peripheral blood cells and reactivate later in immunocompromised patients, and this may be criteria to classify the virus as an opportunistic pathogen 11 . HHV‐6A and HHV‐6B are also responsible for post‐transplant infection complications in patients undergoing kidney and stem cell transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…8 Following initial infection, HHV-6 may spread in peripheral blood cells and reactivate later in immunocompromised patients, and this may be criteria to classify the virus as an opportunistic pathogen. 11 HHV-6A and HHV-6B are also responsible for post-transplant infection complications in patients undergoing kidney and stem cell transplantation. They have been observed in bone marrow and solid tissue transplant recipients.…”
mentioning
confidence: 99%